The literary theory toolkit : a compendium of concepts and methods - Rapaport, Herman, 1947- (Malden, MA : Wiley-Blackwell, 2011)
"The Literary Theory Toolkit offers readers a rich compendium of key terms, concepts, and arguments necessary for the study of literature in a critical-theoretical context. Includes varied examples drawn from readily available literary texts spanning all periods and genres Features a chapter on performance, something not usually covered in similar texts Covers differing theories of the public sphere, ideology, power, and the social relations necessary for the understanding of approaches to literature"--
"Without a proper grasp of its relevant theories, approaches, and technical language, an effective analysis and interpretation of literature can be a daunting task. The Literary Theory Toolkit offers readers a rich compendium of key terms, concepts, and arguments necessary for the study of literature in a critical-theoretical context. Author Herman Rapaport provides a lucid overview of the field of literary study and presents readers with the intellectual tools necessary to construct an effective foundation for literary analysis and a richer appreciation of world literature. Topics covered include narrative, poetic, and performance analysis; the study of textual systems; and key aspects of social theory relevant to literary study. With varied examples drawn from literary texts spanning all periods and genres, this toolkit is lively and essential reading for all students of literary theory"--
Machine generated contents note: Preface -- Chapter 1: Introductory Tools for Literary Analysis -- 1.1. Basics -- 1.2. Common Critical Practices -- 1.3. Literary Language -- 1.4. Hermeneutics -- 1.5. Major 20th Century Schools of Critical Analysis -- 1.6. Socio-Political Analyses -- Chapter 2: Tools for Reading Narrative -- 2.1. Story and Plot: Fabula and Syuzhet -- 2.2. Order -- 2.3. Mimesis/Diegesis -- 2.4. Free Indirect Discourse -- 2.5. Interior Monologue -- 2.6. Diachronic and Synchronic -- 2.7. Intertextuality -- 2.8. Dialogism -- 2.9. Chronotope -- 2.10. Character Zone -- 2.11. Focalization -- 2.12. Narrative Codes -- Chapter 3: Tools for Reading Poetry -- 3.1. Tropes -- 3.2. Elision -- 3.3. Resemblance -- 3.4. Objective Correlative -- 3.5. Language Poetry -- 3.6. The New Sentence -- 3.7. Sound Poetry/Concrete Poetry -- 3.8. Prosody -- Chapter 4: Tools for Analyzing Performance -- 4.1. Performance Studies -- 4.2. Realist Theatre: Total Acting -- 4.3. Konstantin Stanislavski -- 4.4. Lee Strasberg (The Method), David Mamet (Practical Aesthetics), Mary Overlie (The Six Viewpoints Approach) -- 4.5. Epic Theatre -- 4.6. Theater of Cruelty -- 4.7. Actions -- 4.8. Play -- 4.9. Happenings -- 4.10. Performance Art -- 4.11. Guerrila Theatre -- Chapter 5: Tools for Reading Texts as Systems -- 5.1. Aristotle and Form -- 5.2. The Literary Work as Object of Rational Empiricism -- 5.3. Saussurean Linguistics -- 5.4. Levi-Strauss and Structuralism -- 5.5. Roman Jakobson's Communication Model -- 5.6. Roland Barthes' Hierarchical Structures -- 5.7. Ideality and Phenomenology of the Literary Object: Husserl and Derrida -- 5.8. Dissemination -- 5.9. Structure as Rhizome: Deleuze and Guattari -- 5.10. Permutation -- 5.11. Undecidability: Derrida, Gödel, Lacan -- 5.12. Simulating Systems: Baudrillard -- 5.13. Multiplicity: Badiou -- Chapter 6: Tools for Social Analysis -- 6.1. The Public Sphere -- 6.2. Ideology -- 6.3. Theories of Power -- 6.4. The Social Relation.
Includes bibliographical references and index.
Keywords: Literature -- History and criticism -- Theory, etc; LITERARY CRITICISM / General